PENGARUH PEMBELAJARAN INKUIRI TERBIMBING BERBASIS SETS TERHADAP HASIL BELAJAR KIMIA PADA MATERI LARUTAN PENYANGGA - Dewi Fitriyani; Zulmanelis Darwis; Irma Ratna Kartika (LPPM Universitas Negeri Jakarta, 2017)
This study aims to determine of learning result in Guided Inquiry based SETS for buffer solution. The research conducted was SMA 55 Jakarta carried in 3th of April to 24th of Mar 2017. The study used purposive sampling technique, from three class taken two classes obtained XI MIA A was treated as the experimental group using the Guided Inquiry learning based SETS, obtained class XI MIA B was treated as control group using the Guided Inquiry. The study used post-test group design. Test instruments used essay. Data of test instrument result,analyzed by statistical analysis test is comparison test of both class post-test value. The result is t-count = 1,868 while the t-table value at 5% significance level is 1,669. The concluded that there is influence of student learning result by using guided inquiry based on SETS. Keywords : guided inquiry learning based SETS, learning result